2020
DOI: 10.1002/jso.26120
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sarcopenia on perioperative complications in abdominally based free‐flap breast reconstruction

Abstract: Purpose: The identification of patient-specific risk factors, which predict morbidity following abdominally based microvascular breast reconstruction is difficult. Sarcopenia is a proxy for patient frailty and is an independent predictor of complications in a myriad of surgical disciplines. We predict that sarcopenic patients will be at higher risk for surgical complications following abdominally based microvascular breast reconstruction. Methods: A retrospective study of all patients who underwent delayed abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…A study on morbidity after rectal cancer surgery found similar results as our study with higher incidence of complications CD grade ≥ III among patients with sarcopenic obesity (OR adjusted = 3.77, 95%CI = 1.1; 12.7) [ 11 ]. Some studies on SMD used different absolute cut-off values for SMD and are thereby difficult to compare to our results [ 29 , 30 , 31 , 32 ]. In one study assessing SMD in patients treated for rectal cancer, outcome was also compared for those with SMD below and above the median, similar to the current study, which was 40HU for our study group.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…A study on morbidity after rectal cancer surgery found similar results as our study with higher incidence of complications CD grade ≥ III among patients with sarcopenic obesity (OR adjusted = 3.77, 95%CI = 1.1; 12.7) [ 11 ]. Some studies on SMD used different absolute cut-off values for SMD and are thereby difficult to compare to our results [ 29 , 30 , 31 , 32 ]. In one study assessing SMD in patients treated for rectal cancer, outcome was also compared for those with SMD below and above the median, similar to the current study, which was 40HU for our study group.…”
Section: Discussionmentioning
confidence: 77%
“…In one of these studies an increased complication incidence, hospital stay and ICU length of stay was found in women with sarcopenia versus women without sarcopenia [ 29 ]. In the other study, no difference in complication incidence was found related to sarcopenia [ 30 ]. The relation between sarcopenic obesity, decreased SMD and increased risk of postoperative complications has been recognized earlier among patients undergoing other types of major surgery.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have read with great interest the comments of Drs. Binay Safer and Safer regarding our recently published article, “The effect of sarcopenia on perioperative complications in abdominally based free‐flap breast reconstruction.” 1 We thank the authors for their comments and are very grateful to them for giving us the opportunity to further discuss the methodology of our study.…”
mentioning
confidence: 99%
“…The authors concluded that sarcopenia, which can reliably be discerned by routine, preoperative abdominal computed tomography (CT) scans, was not related to minor or major surgical complications in patients who undergo abdominally based microvascular breast reconstruction. 1 Sarcopenia has been extensively studied in patients undergoing oncologic procedures, however diagnostic approach in these trials has ongoing discussions. [2][3][4] So, we would like to address some methodological points in this manuscript.…”
mentioning
confidence: 99%